Objective but Not Subjective Short Sleep Duration Is Associated With Hypertension in Obstructive Sleep Apnea. Issue 3 (September 2018) - Ren, Rong; Covassin, Naima; Yang, Linghui; Li, Yun; Zhang, Ye; Zhou, Junying; Tan, Lu; Li, Taomei; Li, Xiao; Wang, Yanyan; Zhang, Jihui; Wing, Yun-Kwok; et al.
Abstract : Extremes of sleep duration and obstructive sleep apnea (OSA) are both associated with hypertension. We aimed to explore whether sleep duration modifies the relationship between OSA and prevalent hypertension, using both objective and subjective measures of total sleep duration. A total of 7107 OSA patients and 1118 primary snorers were included in the study. Hypertension was defined based either on direct blood pressure measures or on diagnosis by a physician. Objective sleep duration was derived by polysomnography and subjective sleep duration was self-reported. Logistic regression models were used to estimate the associations between objective/subjective sleep duration and hypertension prevalence in OSA and primary snorers. Compared with primary snorers, OSA combined with objective sleep duration of 5 to 6 hours increased the odds of hypertension by 45% (odds ratio, 1.45; 95% confidence interval, 1.14–1.84), whereas OSA combined with objective sleep duration <5 hours further increased the odds of hypertension by 80% (odds ratio, 1.80; 95% confidence interval, 1.33–2.42). These results were independent of major confounding factors frequently associated with OSA or hypertension. In stratified analysis by sleep duration, risk of hypertension in those with extremely short sleep (<5 hours) was not significantly different between OSA and primary snorers, whereas odds were significant for OSA in the other 4 sleep duration strata (5–6, 6–7, 7–8, and >8 hours). No significance was evident using subjective sleep duration. We conclude that objective short sleep duration is associated with hypertension in OSA patients. Extremely short sleep duration in itself may actually be even more detrimental than OSA in terms of hypertension risk. Abstract : Supplemental Digital Content is available in the text.